Analysis of Dental Plaque Removal Effect by Floss Type Using QLF-D - Myoung-Hee Kim; Yu Jin Park; Young Sun Hwang (The Korean Society of Dental Hygiene Science, 2022)
Background: The use of dental floss is associated with a reduction in dental caries and periodontal disease. According to personal preference, not only thread type but also C type and Y type floss are used. Although the effectiveness of dental floss for removing dental plaque has been proven, plaque removal effect of C type and Y type floss has not been well reported. In this study, the plaque removal effect of C type and Y type floss compared to thread type floss was experimentally verified.Methods: Thread type, C type and Y type floss were used to remove dental plaque. Ten people in each flossing group participated, and by applying dental floss to the 6 incisors of the maxilla and mandible, the degree of dental plaque was analyzed by QLF-D. To evaluate the removal degree of dental plaque before and after flossing, Simple Plaque Score (SPS), Area R30, Area R70, and Area R120 score were measured. Results: In the analysis using the Area R30 fluorescence score of the QLF-D system, the degree of plaque removal according to the application of dental floss was effective in all the thread type (p=0.018), C-type (p=0.012), and Y-type (p=0.012) floss groups compared to before the application of the floss. Among them, C type floss was more effective in removing plaque than thread type and Y type floss. However, the plaque removal effect between the three floss types was not significantly different in ∆SPS (p=0.674), ∆Area R30 (p=0.726), ∆Area R70 (p=0.504), and ∆Area R120 scores (p=0.423). Conclusion: Thread type, C type, and Y type floss were all effective in removing dental plaque, but there was no significant difference in dental plaque removal effect according to the type of floss.